Digital Image Compositing Fundamentals - Jackson, Wallace (Apress : Imprint: Apress, 2015)
Digital Image Compositing Fundamentals introduces the reader to the concepts and terminology behind digital imaging, including pixels, channels, layers, compositing, alpha, masking, compression, blending, dithering, color depth and the like. What You'll Learn: What are the most common memes in digital imaging  What comprises a digital image compositing pipeline What are the concepts behind digital imaging How to install and use GIMP 2.8 or 2.9 What are and how to use the concepts behind color depth and image optimization.